Calculation of the relative metastabilities of proteins in subcellular compartments of Saccharomyces cerevisiae - Dick, Jeffrey (BioMed Central Ltd., 2009)
Background: Protein subcellular localization and differences in oxidation state between subcellular compartments are two well-studied features of the cellular organization of S. cerevisiae (yeast). Theories about the origin of subcellular organization are assisted by computational models that can integrate data from observations of compositional and chemical properties of the system. Presentation and implications of the hypothesis: I adopt the hypothesis that the state of yeast subcellular organization is in a local energy minimum. This hypothesis implies that equilibrium thermodynamic models can yield predictions about the interdependence between populations of proteins and their subcellular chemical environments. Testing the hypothesis: Three types of tests are proposed. First, there should be correlations between modeled and observed oxidation states for different compartments. Second, there should be a correspondence between the energy requirements of protein formation and the order the appearance of organelles during cellular development. Third, there should be correlations between the predicted and observed relative abundances of interacting proteins within compartments. Results: The relative metastability fields of subcellular homologs of glutaredoxin and thioredoxin indicate a trend from less to more oxidizing as mitochondrion – cytoplasm – nucleus. Representing the overall amino acid compositions of proteins in 23 different compartments each with a single reference model protein suggests that the formation reactions for proteins in the vacuole (in relatively oxidizing conditions), ER and early Golgi (in relatively reducing conditions) are relatively highly favored, while that for the microtubule is the most costly. The relative abundances of model proteins for each compartment inferred from experimental data were found in some cases to correlate with the predicted abundances, and both positive and negative correlations were found for some assemblages of proteins in known complexes. Conclusion: The results of these calculations and tests suggest that a tendency toward a metastable energy minimum could underlie some organizational links between the chemical thermodynamic properties of proteins and subcellular chemical environments. Future models of this kind will benefit from consideration of additional thermodynamic variables together with more detailed subcellular observations.